Real-time Systems' Quality of Service Introducing Quality of Service Considerations in the Life Cycle of Real-time Systems - Gumzej, Roman (Springer London : Imprint: Springer, 2010)
Quality of product has always been an important consideration for any producer, but now increasingly sophisticated products are spurring a growth in the importance of quality of service. Real-time Systems' Quality of Service examines the attainability of efficiency, economy, and ease of use, which make up the quality of service of technologically advanced products. Since production processes have a significant impact on the quality of products, interest is now focused on their control systems, for which a number of quality criteria must be observed during their real-time operation. Quality of service of a real-time system is dependent on the quality of its design and development process; hence, guidelines on how to integrate its parameters with this process are of the utmost importance in achieving the desired system quality. Real-time Systems' Quality of Service reviews the state of the art in quality of service evaluation for real-time systems. It gives a classification of the relevant parameters for quality of service evaluation and also determines the critical points in the design and development process of real-time systems - where performance criteria should be applied or checked. Then, software development and certification standards are assessed, and finally the authors elaborate on how the suggested criteria should be applied to the design, development, and certification process of real-time systems. Real-time Systems' Quality of Service will guide researchers and postgraduates in embedded and real-time systems through the process of introducing quality of service parameters into real-time systems.